Video-Based Finger Puppet Making Training for ECE Parents: A Technology-Enhanced Approach to Home–School Partnership - Anni Risnawati; Heris Hendriana; Sri Nurhayati; Damola Olugbade; Mohammad Moreb (IJECA (International Journal of Education and Curriculum Application), 2025)
Parental engagement is a key determinant of early childhood development, yet many families face practical and psychological barriers to meaningful involvement in their children’s education. This study addresses this gap by rigorously exploring the impact of a video-based finger puppet-making training initiative on parental engagement within early childhood education (ECE) contexts. The study involved five parents from a semi-urban ECE center in Indonesia, each with varying levels of education and digital literacy, providing insight into the program’s accessibility and relevance across diverse backgrounds. Employing a qualitative case study methodology, the research drew on semi-structured interviews, direct observations, and analysis of participant-produced artifacts. Thematic analysis revealed four principal outcomes: First, participants reported heightened self-efficacy in crafting practices, with video-based scaffolding enabling skill development at an individualized pace. Second, the finger puppet activity fostered emotionally resonant storytelling and strengthened literacy practices at home. Third, the training led to increased and more substantive engagement with educators, suggesting an emergent co-educator role among caregivers. Lastly, the asynchronous video format was effective in accommodating diverse schedules and technological capacities, although minor digital access limitations were noted. This study’s findings corroborate and extend scholarship on adult learning theory, symbolic interactionism, and digital pedagogy. Practically, the low-cost, flexible nature of the intervention demonstrates significant potential for broader adoption in diverse ECE contexts, supporting inclusive parent engagement policies. The results offer actionable insights for educators and policymakers seeking to implement scalable, culturally responsive strategies to bridge home–school learning.